Green Zeolite Synthesis Assisted with Plants Extract - Dee Tee; Azhar, Faiz Hafeez; Harun, Zawati; Hussin, Rosniza; Bahri, Syamsutajri Syamsol; Hairom, Nur Hanis Hayati; Ainuddin, Ainun Rahmahwati; Basri, Hatijah; Kamdi, Zakiah (Emerging Advances in Integrated Technology, 2023)
The study explores the hydrothermal synthesis of zeolite using kaolin clay from Perak in the presence of two different reduction mediums, namely turmeric extract and ginger extract, and a 2M NaOH solution, measuring their efficiency and potential for green synthesis. Before the zeolite synthesis and transformation, the kaolin clay was heated at a temperature of 650 oC for 4 hours in the furnace to produce the metakaolin phase. The synthesized zeolite involves the reaction of NaOH with potential reduction plant extracts to assist the transformation of zeolite. The characterization of the synthesized particles after being ground into a fine powder and subsequently undergoing testing and characterization via X-ray diffraction (XRD) revealed the existence of zeolite phases in both plants with slightly different zeolite compositions. Synthesis mixtures with turmeric plants show better composition of the zeolite phase as compared to ginger mixtures. Scanning Electron Microscope (SEM) and Energy Dispersive X-Ray Analysis (EDX) also revealed that the synthesized product using turmeric plant extract was able to produce zeolite LTA with a good grade. The current experimental work shows the possibility of obtaining a well crystalline zeolite from Malaysian kaolin, assisted with plant extract reduction medium.